Analisis Penanganan krisis Cover Corporation terhadap reputasi citra jenama Hololive Production di kalangan pegiat VTuber - Abyan Hidayatullah, Muhammad (Mutiara: Multidiciplinary Scientifict Journal, 2025)
In the development of the digital entertainment world, YouTube is one of the most popular platforms among younger generations. Over time, it has offered a variety of content types, with one of the most popular in recent years being Virtual YouTubers or VTubers. VTubers are YouTubers who create content using avatars or icons in the form of 2D or 3D characters, which do not represent their real appearance. VTubers can operate independently, where they manage their activities on their own, or through an agency, where they are affiliated with a company that manages their activities. Cover Corporation is one such company specializing in this field. However, in their operations, they have faced crises that threaten their image in managing their VTuber agency, Hololive Production. This study analyzes Cover Corporation's strategies in maintaining their reputation